The decision-making journey of Malaysian women with early breast cancer: a qualitative study - Abdullah, A.; Abdullah, K.L.; Yip, C.H.; Teo, S.H.; Taib, N.A.; Ng, C.J. (2013)
Background: The survival outcomes for women presenting with early breast cancer are influenced by treatment decisions. In Malaysia, survival outcome is generally poor due to late presentation. Of those who present early, many refuse treatment for complementary therapy. Objective: This study aimed to explore the decision making experiences of women with early breast cancer. Materials and Methods: A qualitative study using individual in-depth interviews was conducted to capture the decision making process of women with early breast cancer in Malaysia. We used purposive sampling to recruit women yet to undergo surgical treatment. A total of eight participants consented and were interviewed using a semi-structured interview guide. These women were recruited from a period of one week after they were informed of their diagnoses. A topic guide, based on the Ottawa decision support framework (ODSF), was used to facilitate the interviews, which were audio recorded, transcribed and analysed using a thematic approach. Results: We identified four phases in the decision-making process of women with early breast cancer: discovery (pre-diagnosis); confirmatory ('receiving bad news'); deliberation; and decision (making a decision). These phases ranged from when women first discovered abnormalities in their breasts to them making final surgical treatment decisions. Information was vital in guiding these women. Support from family members, friends, healthcare professionals as well as survivors also has an influencing role. However, the final say on treatment decision was from themselves. Conclusions: The treatment decision for women with early breast cancer in Malaysia is a result of information they gather on their decision making journey. This journey starts with diagnosis. The women's spouses, friends, family members and healthcare professionals play different roles as information providers and supporters at different stages of treatment decisions. However, the final treatment decision is influenced mainly by women's own experiences, knowledge and understanding.